Group Theory for High Energy Physicists. - Saleem, Mohammad (CRC Press, 2012)
Elements of Group Theory Definition of a Group Some Characteristics of Group ElementsPermutation Groups Multiplication Table Subgroups Power of an Element of a Group Cyclic Groups Cosets Conjugate Elements and Conjugate Classes Conjugate Subgroups Normal Subgroups Centre of a Group Factor Group Mapping Homomorphism Kernel Isomorphism Direct Product of Groups Direct Product of Subgroups Group Representations Linear Vector Spaces Linearly Independent Vectors Basic Vectors Operators Unitary and Hilbert Vector Spaces Matrix Representative of a Linear Operator Change of Basis and Matrix Representat.